A healthy plant-based diet from adolescence towards young adulthood: psychosocial determinants and nutrient intake/status correlates. (2020) - Michels, Nathalie
Abstract : Introduction: New dietary recommendations focus on a plant-based diet. As dietary habits are formed during adolescence, knowledge on determinants of this food choice in this age-group can help prevention campaigns. Since an unbalanced choice in plant-based food might lead to nutrient deficiencies, it is also crucial to detect its association with nutrient intake and nutrient status. Methods: In 2330 adolescents from the European HELENA study in 2006, a healthy plant-based diet index (hPDI) was calculated based on two 24 h recalls. In Belgium, 69 of them were remeasured in 2016 as young adults. The psychosocial determinants nutritional knowledge, advantages, awareness, social support, social norm, self-efficacy, barriers, availability and intention were tested by multiple linear regression. Nutrient status was determined by 16 markers in fasting blood. Linear regressions with hPDI as predictor and nutrient intake/status as outcome were adjusted for age, sex, socio-economic status, BMI, waist circumference, energy-intake, physical activity and smoking. Results: There was a strong correlation in hPDI after 10 years (Spearman = 0.56, p < 0.001). Determinants for adolescents' plant-based diet were in descending order being a girl(β = 0.245;p < 0.001), a higher BMI(β = 0.140;p < 0.001), knowing the advantages(β = 0.104;p < 0.001), having availability over healthy food(β = 0.100;p < 0.001), high self-efficacy(β = 0.087;p < 0.001), health awareness(β = 0.072, p = 0.004), younger age(β = -0.048;p = 0.015) and better nutritional knowledge(β = 0.046;p = 0.020). In adolescents, hPDI was associated with lower energy intake, especially less overall fat, cholesterol, saturated fatty acids, mono-unsaturated fatty acids, proteins and mono/di-saccharides but more fibre. In micronutrients, higher intake of calcium, iron, magnesium, potassium, zinc, copper, vitamin A, C, E, K but less vitamin B12 and D were detected. Concerning nutrient status, hPDI was related to higher low-density cholesterol, vitamin D, vitamin C and beta-carotene levels. In adults, hPDI was associated with lower energy intake, especially less overall fat, cholesterol, saturated fatty acids and mono-unsaturated fatty acids but more carbohydrates and fibre, magnesium and vitamin C; while not with nutrient status. Longitudinally, we confirmed the link with intake of more fiber, potassium and less cholesterol. Additionally, a longitudinal positive association with poly-unsaturated fat intake was seen. Conclusion: Tracking of hPDI over 10 years proved the importance of targeting these determinants in adolescents. The hPDI was indeed generally linked to a healthier dietary intake, especially more fiber, a healthier fat choice and higher vitamin intake except for lower vitamin B12 and D. Nevertheless, the latter two were not reflected in more deficiencies and nutrient status differences were limited.